Familial small-intestine carcinoids: Chromosomal alterations and germline inositol polyphosphate multikinase sequencing. Issue 1 (January 2017) - de Mestier, Louis; Pasmant, Eric; Fleury, Clémence; Brixi, Hedia; Sohier, Pierre; Féron, Thomas; Diebold, Marie-Danièle; Clauser, Eric; Cadiot, Guillaume; ,
Abstract: Background: Familial small-intestine neuroendocrine tumors (SI-NETs) are an exceptional inherited entity. Underlying predisposing mechanisms are unelucidated, but inositol polyphosphate multikinase ( IPMK ) gene alterations might promote their tumorigenesis. Methods: A retrospective-prospective nationwide cohort was constituted, by including patients with proven SI-NETs and at least one relative with the same disease. We performed constitutional and somatic IPMK sequencing, and somatic DNA comparative genomic hybridization (CGH). Results: We included 17 patients from 8 families, who were characterized by high prevalence (57%) of multiple SI-NETs, and high frequency of distant metastases (82%) and carcinoid syndrome (65%). No IPMK mutation was found in constitutional or tumor DNA. CGH array revealed recurrent chromosome-18 deletions but no alteration in the IPMK region. Conclusion: We report here the first European series of patients with familial SI-NETs. Predisposing mechanisms may not involve the IPMK -encoding sequence or chromosomal region and might not differ from those of sporadic SI-NETs.